Cultivating Compassion 慈: A Daoist Perspective - Culham, Tom (Paideusis, 2014)
The purpose of this paper is to make a contribution to our working knowledge, practice and pedagogy of compassion through consideration of a Daoist perspective on the matter. I begin with a consideration of Daoist cosmology and a sage’s compassion drawn primarily from the Daodejing, This serves as a backdrop to consider Daoist contemplative pedagogy for the cultivation of virtue and compassion. Consistent with Daoist practices which rely on exemplars as a means of inspiring others I justify considering Nelson Mandela an exemplar of compassion. I then discuss how his life lines up with the Daoist conception of compassion. Finally I discuss the practicalities of developing compassion along with other virtues in post-secondary business ethics education classes. These classes work with the following principles: starting small, self- compassion, person to person connections and relationship. Students engage in emotional intelligence activities including: exercises to know their purpose or calling, meditative exercises that help them become aware of their emotions, and structured interpersonal interaction challenging them to develop new social skills. While this work is in its early stages it appears to assist students in developing compassion for others.